Horizontal Coalition Stability Analysis of Supply Chain Entities Based on Sequential Game - Shizhao Wang; Yong Luo (Discrete Dynamics in Nature and Society)
Aiming to find the effect of the same status entities’ horizontal coordination on supply chain, this paper studied the coalition stability of dealers in a two-stage supply chain with one supplier and multiple dealers. First, a vertical sequential game model is built, where the supplier is leader and the multiple dealers are followers. In the second stage of the game, multiple dealers face two selections: playing Nash game with each other or developing a coalition. Then, according to the results acquired by comparing the dealers’ profits which depend on their coalition situations, the criterion of coalition stability is developed. Finally, numerical simulation is used to verify the validity of the model, and some insights are obtained. For example, if the sensitivity coefficient T of the market price is fixed, dealers’ coalition tends to be stable with the increasing of the substitution rate k in a reasonable range; the supplier’s optimal wholesale price is constant with and without dealer’s coalition, but dealers’ coalition causes demand to decrease, which leads to the decrease of the supplier’s profit too. The result of this paper provides an important reference for the formation of dealers’ coalition in IT or automobile supply chain.